Software para apoyar el aprendizaje de fundamentos de programación basado en gamificación - Rodríguez Cherrez, Manna Neumane (2020)
This project has been developed to help teachers and students in the process of teaching and learning of coding basic concepts using gamification. Many learners who studying study subjects related to programming have learning issues, which sometimes lead to desertion. Therefore, educational institutions and teachers, are constantly looking for new strategies and digital tools to improve students’ performance. Although there are several tools for teaching coding, none of them focuses the analysis and creation of questions based on the same coding block. Code analysis is a common activity in computer programming learning. Over the class, students and teachers are able to analyze a code. This software tool intends to support students and teachers in the teaching-learning process of computer programming basics. It helps develop logical reasoning, enhance desktop testing, and promote code analysis. For this, ludic activities are used such as answering questions with time limits, ordering puzzles and mentally solving algorithms, "competing" against other students. The approach started by defining aesthetic and functional requirements and guidelines through interviews and similar applications analysis. After that, a prototype was built, which was evaluated in order to know its usability level. It was found that the software is widely accepted as a good tool. In general, the surveyed students answered with high scores to the survey questions (4 of 5 average). The teachers who participated also gave positive reviews such as the potential usefulness of the software. These results allow us to infer that the proposal could become a valuable support tool in learning programming basics. Keywords: gamification, teaching-learning, programming basic concept, guidelines, requirements, prototype, stakeholders, usability test evaluation.